The isolation and mapping of a novel hydroxycinnamoyltransferase in the globe artichoke chlorogenic acid pathway - Comino, Cinzia; Hehn, Alain; Moglia, Andrea; Menin, Barbara; Bourgaud, Frédéric; Lanteri, Sergio; Portis, Ezio (BMC plant biology, 2009)
Background The leaves of globe artichoke and cultivated cardoon ( Cynara cardunculus L.) have significant pharmaceutical properties, which mainly result from their high content of polyphenolic compounds such as monocaffeoylquinic and dicaffeoylquinic acid (DCQ), and a range of flavonoid compounds. Results Hydroxycinnamoyl-CoA:quinate hydroxycinnamoyltransferase (HQT) encoding genes have been isolated from both globe artichoke and cultivated cardoon (GenBank accessions DQ915589 and DQ915590, respectively) using CODEHOP and PCR-RACE. A phylogenetic analysis revealed that their sequences belong to one of the major acyltransferase groups (anthranilate N-hydroxycinnamoyl/benzoyltransferase). The heterologous expression of globe artichoke HQT in E. coli showed that this enzyme can catalyze the esterification of quinic acid with caffeoyl-CoA or p -coumaroyl-CoA to generate, respectively, chlorogenic acid (CGA) and p -coumaroyl quinate. Real time PCR experiments demonstrated an increase in the expression level of HQT in UV-C treated leaves, and established a correlation between the synthesis of phenolic acids and protection against damage due to abiotic stress. The HQT gene, together with a gene encoding hydroxycinnamoyl-CoA:shikimate/quinate hydroxycinnamoyltransferase (HCT) previously isolated from globe artichoke, have been incorporated within the developing globe artichoke linkage maps. Conclusion A novel acyltransferase involved in the biosynthesis of CGA in globe artichoke has been isolated, characterized and mapped. This is a good basis for our effort to understand the genetic basis of phenylpropanoid (PP) biosynthesis in C. cardunculus .